Microshear Bond Strength of Transbond XT and Assure Universal Bonding Resin to Stainless Steel Brackets, Amalgam and Porcelain - Gholamreza Eslami Amirabadi; Maryam Shirazi; Zahra Shirazi (Islamic Dental Association of Iran, 2015)
Background and Aim: Assure Universal Bonding Resin is marketed with fluoride releas-ing potential. The manufacturer claims that it provides adequate bond strength between the bracket and amalgam and porcelain. This study compared the shear bond strength of Transbond XT and Assure Universal Bonding Resin to stainless steel brackets, amalgam and porcelain in vitro. Materials and Methods: In this in vitro study, 20 standard brackets of the maxillary cen-tral incisors, 20 feldspathic porcelain specimens and 20 self-cure acrylic cavities filled with amalgam were divided into 2 groups bonded with Transbond XT and Assure. After surface preparation in each group, Transbond XT composite was applied to the surfaces using silicon tubes and light-cured for 20 seconds. Then, the microshear bond strength was measured using a universal testing machine. The data were subjected to two-way ANOVA, Tukey's post hoc test, Student's t-test and the Kruskal Wallis test. Results: Different microshear bond strength values were obtained for the bond to stain-less steel brackets, amalgam and porcelain by Transbond XT and Assure (p<0.000). Using Assure for bonding to amalgam (7.2±1.46 vs. 10.12±4.97) and brackets (16.14±3.2 vs. 20.16±5.12 p<0.05) decreased the microshear bond strength compared to Transbond XT. However, Assure significantly increased the bond strength to porcelain compared to Transbond XT (28.84±6.42 vs. 22.48±3.6 p<0.01). Non-parametric Kruskal-Wallis test showed significant differences in adhesive remnant index (ARI) between the two bonding agents only in the amalgam group (p=0.029). Conclusion: Although the bond strength values of Assure were less than those of Transbond XT, Assure was capable of providing sufficient bond strength especially to porcelain.